Zmiany strukturalne (Strukturwandel) w niemieckim prawie cywilnym a perspektywa polska - Bierecki, Dominik (PRAWO i WIĘŹ, 2026)
The paper analyses the German concept of structural change (Strukturwandel) in civil law and assesses the prospects for its occurrence in Polish civil law. This concept is based on inductive reasoning and consists in the observation of the evolving meaning of legal principles and institutions in response to socio-economic transformations. The research thesis of the paper holds that structural changes in both German and Polish law find their justification in the pursuit of contractual balance. The paper employs three research methods: the theoretical-legal method – in the analysis of German legal scholarship; the comparative method – through references to German civil law; and the dogmatic-legal method – in the analysis of the norms of Polish civil law. The conclusions indicate that structural change is not an exclusively Germanic phenomenon, but affects all systems of civil law responding to the need to strengthen the protection of the weaker parties to obligational relationships. The common denominator of this change in both legal orders remains the safeguarding of contractual balance.